The deer and the woodcutter a Korean folktale - Kim, So-un 1907- (Tuttle Pub., 2005)
After tricking a fairy into becoming his bride, a woodcutter pays dearly for his treachery in this Korean folktale that explains why the rooster looks to the sky and crows loudly at dawn.